2009
DOI: 10.1038/ejhg.2009.72
|View full text |Cite
|
Sign up to set email alerts
|

Split hand/foot malformation due to chromosome 7q aberrations(SHFM1): additional support for functional haploinsufficiency as the causative mechanism

Abstract: We report on three patients with split hand/foot malformation type 1 (SHFM1). We detected a deletion in two patients and an inversion in the third, all involving chromosome 7q21q22. We performed conventional chromosomal analysis, array comparative genomic hybridization and fluorescence in situ hybridization. Both deletions included the known genes associated with SHFM1 (DLX5, DLX6 and DSS1), whereas in the third patient one of the inversion break points was located just centromeric to these genes. These observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 30 publications
(48 reference statements)
4
46
0
Order By: Relevance
“…Addition-ally, breakpoints analysis revealed that the proximal breakpoint of the present deletion lies just 88 kb downstream of the DLX5 gene. Because haploinsufficiency for DLX5 and DLX6 genes appears to be responsible for ectrodactyly [Scherer et al, 1994;van Silfhout et al, 2009], our observation indirectly confirms the exclusion of the CUX1 gene (as suggested by Bernardini et al [2008]) and potential regulatory elements (as suggested by Tzschach et al [2007]) downstream of DLX5 and ACN9 (between RP11-800O14 and D7S618) in determining such a limb defect.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Addition-ally, breakpoints analysis revealed that the proximal breakpoint of the present deletion lies just 88 kb downstream of the DLX5 gene. Because haploinsufficiency for DLX5 and DLX6 genes appears to be responsible for ectrodactyly [Scherer et al, 1994;van Silfhout et al, 2009], our observation indirectly confirms the exclusion of the CUX1 gene (as suggested by Bernardini et al [2008]) and potential regulatory elements (as suggested by Tzschach et al [2007]) downstream of DLX5 and ACN9 (between RP11-800O14 and D7S618) in determining such a limb defect.…”
Section: Discussionsupporting
confidence: 73%
“…Diverse deletions within the 7q21q32 segment have often been associated with ectrodactyly and multiple clinical features, such as intellectual disability/developmental delay, ear/hearing anomalies, low birth weight, feeding problems, unusual cry, microcephaly, micrognathia, cardiac and palate defects, recurrent infections, abnormal palmar creases, and eye abnormalities [Young et al, 1984;Rivera et al, 1991;Scherer et al, 1994;Montgomery et al, 2000;Bernardini et al, 2008;Cheong et al, 2008;van Silfhout et al, 2009]. This phenotypic consistency along with the apparent overlapping of the deleted regions may indeed represent a recognizable deletion syndrome [Fagan et al, 1989].…”
mentioning
confidence: 99%
“…30 A position effect was most likely responsible for the split-hand-feet syndrome (SHFM) in patient 37 with an inversion breakpoint in 7q near the SHFM1 locus and the candidate genes DSS1, DLX5 and DLX6. 31 …”
Section: Clinical Significance Of the Detected Imbalancesmentioning
confidence: 99%
“…Interestingly, an individual with PDD-NOS and SHFM1 has an inversion in the DYNC1I1 region (chr 7: 95.53-95.72 Mb) (Fig. 5), whose breakpoint has not been finely characterized (van Silfhout et al 2009). Further analysis would be required in order to establish whether the PDD-NOS and SHFM phenotypes in this individual could be due to the disruption of both the DYNC1I1 gene and our characterized eExons.…”
Section: Exonic Enhancers Of Nearby Genesmentioning
confidence: 99%